2014
DOI: 10.3109/01443615.2014.930108
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes with a primary complaint of perception of reduced fetal movements

Abstract: Reduced fetal movement is a worrisome common complaint, not only for mothers but also for the attending medical personnel. The aim of this study was to analyse the pregnancy outcomes of women who presented primarily with reduced fetal movements (RFM). A retrospective study was performed based on patients' perception alone. Obstetric, past medical history, current presentation and outcomes of pregnancy were analysed. A total of 230 case notes were reviewed, with the majority being primigravidae. Less than half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This finding is in line with the fact that this group had more cases of poor outcome (Group A -80%, group B -12%, group C 8%). Our results are in accordance with Nor Azlin et al 10 study, who analyzed 230 cases of women who presented primarily with reduced fetal movements. Less than half (49%) of the women had spontaneous labor, 48% had induction and 6% had elective caesarean section.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with the fact that this group had more cases of poor outcome (Group A -80%, group B -12%, group C 8%). Our results are in accordance with Nor Azlin et al 10 study, who analyzed 230 cases of women who presented primarily with reduced fetal movements. Less than half (49%) of the women had spontaneous labor, 48% had induction and 6% had elective caesarean section.…”
Section: Discussionsupporting
confidence: 93%
“…Although it is well known that multiparous women perceive fetal movements earlier than nulliparous women, it is yet unclear whether there is an association between parity and diminished maternal perception of fetal movement . Some argue that DFM is more prevalent among primiparous women , whereas others suggest that there is no difference in fetal movement sensation in association with parity . The similar rate of DFM among the groups may be explained by the various factors affecting fetal movement sensation, such as maternal weight, placental implantation site, amniotic fluid volume, and gestational age , and the possible interaction between these factors.…”
Section: Discussionmentioning
confidence: 97%
“…For multiparous women, we found that DFM was associated with increased risk of unscheduled CD, mostly indicated by intermediate/abnormal fetal heart rate tracing, with no immediate adverse perinatal outcome. Several studies have also demonstrated no additional risk for all‐cause CD among women with DFM, although these studies were limited by small study populations . Daly et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden 2014, 463 babies were stillborn after gestational week 22, and another 175 babies died within 28 days after birth [ 7 ]. Maternal perception of decreased fetal movements is subjective and commonly used to assess fetal well-being [ 8 ]. Studies indicate an association between a low awareness of the fetal movements and negative pregnancy outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%